New guidelines for a more accurate extraction of solar cells and modules key data from their current–voltage curves. (10th February 2017) - Paviet‐Salomon, Bertrand; Levrat, Jacques; Fakhfouri, Vahid; Pelet, Yanik; Rebeaud, Nicolas; Despeisse, Matthieu; Ballif, Christophe
Abstract: This paper investigates the optimisation of the fit procedures to determine with the highest accuracy the key data of photovoltaic cells and modules from their current–voltage characteristics. Our analysis is based on numeric current–voltage curves obtained by solving the two‐diode equation in steady state. The established state‐of‐the‐art fit procedures, such as the ASTM E948‐09 standard, are shown to be outperformed by smart adjustments of the fit range and the regression type. As a result of this optimisation, the accuracy in determining the short‐circuit current density is improved by up to 15 times, the open‐circuit voltage by 3 to 10 times and the maximum power by 4 to 5 times, in comparison to state‐of‐the‐art approaches. It is demonstrated that the signal‐to‐noise ratio of the experimental data strongly influences the fit accuracy, and therefore, the fit criteria must be adjusted according to the noise level of the measuring unit. Finally, our fit procedures were applied to experimentally measured current–voltage curves of 3000 silicon heterojunction solar cells. Notably, the established fit standards are shown to overestimate the maximum power by up to 0.2%, whereas our proposed fit yields more consistent values. In conclusion, novel fit guidelines are provided, aiming at enhancing the key data determination of high‐efficiency photovoltaic cells and modules. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : We investigate the optimisation of the fit procedures to determine with the highest accuracy the key data of photovoltaic devices from their current–voltage characteristics. We show that the state‐of‐the‐art fit procedures are outperformed by smart adjustments of the fit range and the regression type. We improve the accuracy in determining the short‐circuit current density by up to 15 times, the open‐circuit voltage by 3 to 10 times, and the maximum power by 4 to 5 times, compared to state‐of‐the‐art approaches.